Actuated 3D microgels for single cell mechanobiology. Issue 10 (19th April 2022) - Özkale, Berna; Lou, Junzhe; Özelçi, Ece; Elosegui-Artola, Alberto; Tringides, Christina M.; Mao, Angelo S.; Sakar, Mahmut Selman; Mooney, David J.
Abstract : A mechanically active microgel platform for single cell mechanobiology is presented. Optically triggered nanoactuators generate isotropic compression in 3D microgels, leading to reversible and mechanosensitive calcium signaling in encapsulated MSCs. Abstract : We present a new cell culture technology for large-scale mechanobiology studies capable of generating and applying optically controlled uniform compression on single cells in 3D. Mesenchymal stem cells (MSCs) are individually encapsulated inside an optically triggered nanoactuator-alginate hybrid biomaterial using microfluidics, and the encapsulating network isotropically compresses the cell upon activation by light. The favorable biomolecular properties of alginate allow cell culture in vitro up to a week. The mechanically active microgels are capable of generating up to 15% compressive strain and forces reaching 400 nN. As a proof of concept, we demonstrate the use of the mechanically active cell culture system in mechanobiology by subjecting singly encapsulated MSCs to optically generated isotropic compression and monitoring changes in intracellular calcium intensity.